Perspectives on flood 1998 - Ahmad, Qazi Kholiquzzaman, 1943- (Dhaka : The University Press, 2000)
Contributed articles presented at a seminar in 1998.
Includes bibliographical references.
Keywords: Floods -- Bangladesh; Flood damage -- Bangladesh; Disaster relief -- Bangladesh; Flood control -- Bangladesh